A gramática das construções mêmicas de Internet no português do Brasil: uma interface da Gramática Sistêmico-Funcional e da Gramática do Design Visual - Santos, Wilquer Quadros dos (Universidade Federal de São Carlos, 2020)
This work aims to investigate, analyze, map and systematize the linguistic and visual characteristics of Memes: a schematic structure of the digital genre known as Meme, particularly taken from the Internet in Brazilian Portuguese, in the interface of the Systemic-Functional Grammar and the Grammar of Visual Design. Since the advent of the Internet and especially of social sharing networks, Meme emerges as a multi-semiotic combination, a multimodal digital expression with a humorous and critical bias. Originally, the zoologist Richard Dawkins created the term meme in 1976 in the book The Selfish Gene. However, the meaning attributed to it on the Internet has distanced itself from the original meaning. This neologism (meme) was created from the root of the Greek word Mimema (imitation) and transposed to the sonority similar to the term gene, taking into consideration the fact that, for Dawkins, the meme is the gene of the culture. Dawkins conceives memes as behavioral replicators, transmission units and cultural imitation. For the author, memes are responsible for the propagation of facts, reproduction of thought and behavior (DAWKINS, 2017). Methodologically, this research focuses on the analysis and on the description of the verb-visual syntactic configuration of Internet Memes. Taking into consideration the survey of the memic occurrences between the years of 2014 and 2018 in social networks, sites, online repositories and classic models of this digital genre in the Brazilian Portuguese, a mapping of the lexical-grammatical and visual functions that can be typifiers of the genre under analysis is done, as well as the systematizing of the schematic structure of the genre from its linguistic and visual aspects, that is, from the textual completeness. In this paper, we analyze the multisemiotic aspect of the Meme from the internet, which has as its main theoretical contribution the authors Blackmore (1999, 2000), Cabral and Fuzer (2014), Dawkins (2017), Gouveia (2009), Halliday (1994, 2001, 2009), Kress and van Leeuwen (1996, 2006), Lima-Lopes (2012), Marcuschi (2001, 2009), Neves (1994, 2001, 2012), Recuero (2007). Finally, it is understood that Memes can typically be verbally composed of material processes, declarative sentences and topical themes. In the visual sphere, verbal narrative and symbolic conceptual processes increase, as well as a Demand type grammar, in the middle plane and from a frontal point of view. Although in a less regular way, the visual syntax is segmented, dividing the given and new information, predominating the color, font and collage as factors of salience. In addition, they can be composed of nominal groups, simple sentences or complex sentences, experiencing suppression and constructional changes. These gaps and variations are recoverable in the context of the situation and in the interface with the visual element.
The grammar of Internet memic construction in Brazilian Portuguese: an interface between Systemic-Functional Grammar and Visual Design Gramma
Keywords: Meme de internet.; Gramática Sistêmico-Funcional.; Gramática do Design Visual; Gêneros digitais; Multimodalidade; Meme from the internet; Systemic-Functional Grammar; Grammar of Visual Design; Digital genre; Multimodality; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA